Development of Digitalization of Semester Learning Plans for Room Reservation Courses in the Room Division Study Program - Muhammad Husni HM; Anak Agung Ngurah Sedana Putra; Dimas Purnama Dewata (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This study aims to examine the importance of digitalization and content development in semester learning plans for room booking courses in the room division study program at the Lombok Tourism Polytechnic. This study uses qualitative research methods with data collection techniques using observation, interviews, focus group discussions, and literature studies. As a result of the study described in this article, to meet the needs of the hotel industry, the RPS for room booking courses at the Lombok Tourism Polytechnic must be updated in accordance with current trends and the needs of the hotel industry. The development of the RPS for guest room reservations is expected to continue continuously so that the implementation of learning courses on guest room reservations, especially in digitalization room reservations in accordance with industry demand so that the absorption of Rooms Division study program graduates by industry can be faster and in line with the competencies expected by the hotel industry